Hashimoto’s thyroiditis is not a risk factor for thyroid cancer - Eshraghi, Mohsen; Mousavi, Seyed Mojtaba (Faculty of Medicine, Trisakti University, 2018)
BackgroundThyroid carcinoma is the most common endocrine malignancy. Chronic inflammation can be involved in tumorigenesis. It is estimated that more than 20% of all tumors are caused by persistent inflammatory conditions. The objective of the present study was to compare the inflammatory factor level of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and thyroiditis between benign and malignant thyroid nodules.MethodsA cross-sectional study was conducted involving 94 patients (47 patients with benign tumors as controls and 47 patients with malignant tumors as cases). ESR and CRP were measured and analyzed. Mean ESR and CRP in both groups was compared using independent t-test. The chi-square test was used to assess the risk of cancer in patients with Hashimoto’s thyroidits and with significance level at p<0.05.ResultsThe mean age of the patients in the benign group was 42.28 ± 13.43 years and in the malignant group 42.20 ± 16.32 (20-85) years, which was not significantly different (p=0.350). Independent t-test results were not significantly different between mean ESR and CRP in both groups (p=0.800 and p=0.993 respectively). Hashimoto’s thyroiditis was not a risk factor for thyroid cancer (OR=1.58; 95% CI:0.63-4.01).ConclusionThis study demonstrated that Hashimoto’s thyroiditis was not a risk factor for thyroid cancer. Factors such as ESR and CRP are acute phase reactants and their levels increase in cases of acute inflammation, but may not increase significantly in chronic inflammatory conditions and malignancies.